ANTIOXIDANT ACTIVITY AND ANTICARCINOGENIC PROPERTIES OF â€œSISIK NAGAâ€(DRYMOGLOSSUM PILOSELLOIDES PRESL.) - Endrini, Susi (Jurnal Kedokteran YARSI, 2009)
The research was conducted to determine the anticarcinogenic properties of ?sisik naga?(Drymoglossum piloselloides Presl.), by the microculture tetrazolium salt (MTT) assay on the human breast carcinoma dependenthormone (MCF-7) cell lines. The preliminary results showed that the ?sisik naga? extract displayed the cytotoxic effects against MCF-7 with IC50 value of 83.63µg/ml. The antioxidative activity of the extracts which could contribute to their cytotoxic properties was also studied. The ?sisik naga? extract was found to have high antioxidant activity with IC50-value of 4.229 ppm. The strong cytotoxic properties of the ?sisik naga? extract could be due to its high antioxidant activity.